2021
DOI: 10.3233/jpd-202297
|View full text |Cite
|
Sign up to set email alerts
|

Does Gut Microbiota Influence the Course of Parkinson’s Disease? A 3-Year Prospective Exploratory Study in de novo Patients

Abstract: Background: Although abnormalities in gut microbiota are hypothesized to influence the pathogenesis and clinical phenotype of Parkinson’s disease (PD), prospective studies on de novo patients are lacking. Objective: To preliminarily investigate whether gut microbiota in early untreated PD may predict motor and non-motor features progression over a 3-year period. Methods: 16S ribosomal RNA gene amplicons were sequenced on fecal samples of 39 de novo PD patients. Multiple confounders were taken into account, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…An earlier study on 36 PD sufferers [60], using real-time PCR rather than next generation sequencing, found that lower counts of Bifidobacterium, Bacteroides, and Clostridium cluster VI were associated with a more rapid deterioration. A 3-year follow up of 25 PD sufferers found an association between the lower levels of Roseburia and Faecalibacterium and higher levels of Actinobacteria and Oscillospira with worsening motor, non-motor and cognitive symptoms [61].…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study on 36 PD sufferers [60], using real-time PCR rather than next generation sequencing, found that lower counts of Bifidobacterium, Bacteroides, and Clostridium cluster VI were associated with a more rapid deterioration. A 3-year follow up of 25 PD sufferers found an association between the lower levels of Roseburia and Faecalibacterium and higher levels of Actinobacteria and Oscillospira with worsening motor, non-motor and cognitive symptoms [61].…”
Section: Discussionmentioning
confidence: 99%
“…However, structural differences between the GM of PD patients and healthy controls have been previously documented and accumulating evidence shows the abundance of certain fecal microbial taxa are differentially distributed among PD patients and healthy controls. Lactobacillus , Bifidobacterium , Verrucomicrobiaceae, and Akkermansia show an increase in PD patients while Faecalibacterium , Roseburia , Coprococcus , Blautia , Prevotella , and Prevotellaceae have lower abundances [ 261 , 262 , 263 , 264 ].…”
Section: Gut Microbiome In Parkinson’s Diseasementioning
confidence: 99%
“…However, structural differences between the GM of PD patients and healthy controls have been previously documented and accumulating evidence shows the abundance of certain fecal microbial taxa are differentially distributed among PD patients and healthy controls. Lactobacillus, Bifidobacterium, Verrucomicrobiaceae, and Akkermansia show an increase in PD patients while Faecalibacterium, Roseburia, Coprococcus, Blautia, Prevotella, and Prevotellaceae have lower abundances [261][262][263][264]. Scheperjans et al, (2015) [265] found that the relative abundance of Prevotellaceae taxa was reduced by nearly 80% in PD patients when compared to controls, and that the abundance of four microbial taxa was able to classify PD patients with over 90% specificity.…”
Section: Gut Microbiome In Parkinson's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…It also showed significant alteration of various functional pathways (such as those associated with xenobiotic metabolism) [ 24 ]. Two long-term observational studies addressed the correlation of gut dysbiosis and the progression of PD in the patient [ 25 , 26 ]. Both assessed the exact distribution of the gut microbiome and observed a correlation between the abnormal distribution of certain gut microflora and the progression of PD symptoms [ 25 , 26 ].…”
Section: Reviewmentioning
confidence: 99%